2013
DOI: 10.4103/1755-6783.121015
|View full text |Cite
|
Sign up to set email alerts
|

A study of patients with type II respiratory failure put on non-invasive positive pressure ventilation

Abstract: Non-invasive ventilation as an alternative to the endotracheal intubation is associated with less infectious complications and injury to the airways. In a study cohort that included 50 patients with type II respiratory failure with the commonest diagnosis of chronic obstructive pulmonary disease (COPD) exacerbation with or without associated co-morbidities, mechanical ventilation with non-invasive positive pressure ventilation (NIPPV) was applied and the response was observed in terms of change in various clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(40 reference statements)
2
4
0
Order By: Relevance
“…No mortality was observed in the patients improved and continued on NIPPV. The success rate in the present study is comparable with the previous studies 14,15,16,27,30 In our study NIPPV was used for a mean duration of 38.5±13 hrs. In the study of Umberto Meduri et al 31 it was 23±17 hrs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No mortality was observed in the patients improved and continued on NIPPV. The success rate in the present study is comparable with the previous studies 14,15,16,27,30 In our study NIPPV was used for a mean duration of 38.5±13 hrs. In the study of Umberto Meduri et al 31 it was 23±17 hrs.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study there was a significant improvement (P<0.0001) in the average PaCO2 levels within 1hr from 67.3± 5.61 to 62.8±5.74. The results obtained are comparable with the other studies 14,16,26 which showed significant decrease in PaCO2 after 1hr of administration of NIV. The change in PaCO2 also reflected in pH with improvements from 7.29±0.02 to 7.31±0.02 (p<0.001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Respiratory rate at admission was significantly higher in the NIPPV failed group as compared with the NIPPV successful group, and this could possibly be used to predict response to NIPPV [23,24].…”
Section: Discussionmentioning
confidence: 95%
“…In present study, mean age among the study population was 49.40 (±9.89) years, Similarly, in the studies by George et al [16] and Lt. Col. Rai et al [17] , the average age of patients enrolled was >50 years. The present study has a male preponderance (68/110) of 61.8%; the study of Agrawal et al [18] and Vanani et al [19] , had a male preponderance of 63% and 86% respectively. The common indication for initiation of NIPPV was COPD 37 (33.63%) followed by Postextubation 30 (27.27%) in present study.…”
Section: Discussionmentioning
confidence: 86%